(untitled) (Journal of Science and Technology Research, 2023)
The present paper investigates heat-flux effect and the dissemination of energy in a rotating bent square micro-channel (MC) subject to a temperature gradient between the vertical sidewalls. The flow structure prevailing the problem is solved by applying a highly accurate spectral-based numerical scheme. The flow controlling parameters are the Dean number (0<Dn≤5000) and the Taylor number (-500 ≤ Tr ≤ 2000) for curvature 0.01 and the Grashof number, Gr=1000. After applying the arc-length path continuation technique to obtain steady solution (SS) curves, two branches of SS consisting of 2- to 8-vortex solutions are prevailed for the non-rotating case while a single branch with a symmetric 2-vortex solution is for positive rotation of the channel. Unsteady flow (UF) properties are simulated by the time-average of the solutions, and the transitional behavior is well predicted by contemplating the power spectrum and phase spaces of the solutions. Results manifest that the UF experiences a consequence ‘steady-state àmulti-periodic àsteady-state’ for no rotation of the channel as Dn is increased. For the rotating case, on the other hand, the flow advances in the scenario ‘steady-state àmulti-periodic àsteady-state’ for negative rotation and only a steady-state solution for rotation in the positive direction. Streamlines and isotherms of SS and UF for various values of the flow-controlling parameters are obtained. Centrifugal force impacts the fluid mixer, which then assists to turn the flow into chaos and prompts to intensify the convective heat transfer (CHT). J. of Sci. and Tech. Res. 4(1): 129-144, 2022